Knowledge and attitudes relating to cervical and breast cancer among women in Maseru, Lesotho - Maseabata M. Ramathebane; Mopa A. Sooro; Richard M. Kabuya; Abdul-Rauf Sayed (AOSIS, 2022)
Background: Cancer has remained one of the leading causes of death worldwide. In Lesotho, breast and cervical cancers contribute about 43% of all the cancer cases annually. Aim: This study is aimed at comparing knowledge, attitudes, and practices between breast and cervical cancers among females in Maseru. Settings: This study consists of women residing in five study sites which have clinics that offer cervical and breast cancer-screening services. Methods: A cross-sectional study was conducted in June 2021 in Maseru, the Capital city of Lesotho. The participants were interviewed using a pre-tested questionnaire, through which their knowledge, practices about, and attitudes towards breast and cervical cancers were assessed. Results: A total of 228 women aged 15-75 years participated in the study and the majority were aged 30 years and above. Of the women interviewed for cervical cancer, 89.5% had heard of it, 11.8% had heard of its screening, and 7.4% had at least one examination. Similarly, for breast cancer, 77.6% of women who had heard of it, 72.9% had heard of screening, and 40.1% of women did at least one examination. Conclusion: The majority of women were more knowledgeable about cervical cancer than breast cancer. However, more women had heard about breast cancer screening than cervical cancer screening. Therefore, there is a need for awareness campaigns related to cervical cancers' screening. Contribution: There is an urgent need to intensify awareness about cervical and breast cancer screening and availability of services at the nearby clinics.